Manajemen Risiko Keselamatan dan Kesehatan Kerja pada Pekerja Produksi Roti di Toko Roti Bread'O Bakery Jatisari, Kota Bekasi Tahun 2021 - Aulia Nur Khairunnisa (2021)
Risk management was conducted so any accidents and illnesses can be avoided. This study was conducted because there were various OSH risk factors in bread production workers that can affect workers health and safety. The management guidelines used for this study are Job Safety Analysis (JSA), Risk Management AS-NZS Standard 4360:2004, and HSG 65. The purpose of this study was to identify the OSH risk and to determine risk management for workers in the bread production section at Toko Roti Bread'O Bakery Jatisari, Kota Bekasi. This study was qualitative and quantitative research with Job Safety Analysis (JSA) method. The instruments for this study was using tools and in-depth interview. The population of this study were six workers in the bread production section, with total sampling as the sampling technique. The result of this study is the Occupational Health Safety (OHS) risk hazards found came from physical, chemical, biological, and ergonomics. The risk management used is the implementation of risk management in high-risk jobs. After preventive and control measures were implemented, most of the workers understand and implement the preventive and control measures that have been given. The recommendations are for the bakery owner to do risk management again and add more preventive and control measures.